Case Report: Primary Mediastinal Large B-Cell Lymphoma Invasion of Extranodal Thyroid Tissue Mimicking Tuberculosis and Confounded by Similar Ultrasonic Appearance - Wang, Ying; Chen, Menghan; Ni, Chen; Tong, Jiahui; Chen, Peijun; Zhang, Ying; Yang, Gaoyi (Frontiers in Oncology, 2022)
Background Primary mediastinal large B-cell lymphoma (PMBCL) is a rare type of diffuse large B-cell lymphoma, which has significant features that overlap with those of Hodgkin’s lymphoma. Ultrasound is a commonly used modality to characterize superficial lymph no5des, and ultrasonic findings are often used to distinguish lymphoma from lymph node tuberculosis in daily clinical practice. Although a common malignancy, lymphoma rarely involves extranodal tissues. Case Presentation Here we report the case of a 42-year-old Chinese male patient with PMBCL who was misdiagnosed with tuberculosis because of extranodal invasion. He visited our hospital for a neck mass that he had been noting for 1 week. Ultrasound revealed multiple enlarged lymph nodes on both sides of the neck. The lesions appeared to involve the surrounding soft tissue and thyroid gland, resembling a tuberculous sinus tract formation. Cervical spine computed tomography showed no obvious abnormalities in the cervical cone or bone damage. Contrast-enhanced ultrasound indicated that one of the enlarged lymph nodes in the right neck was rich in blood supply and exhibited centripetal enhancement, with uniform high enhancement at the peak. The patient underwent two ultrasound-guided punctures; the first puncture was performed for an enlarged lymph node in the right neck at Hangzhou Red Cross Hospital. Hodgkin’s lymphoma was suspected based on pathological and immunohistochemical findings, whereas a rare type of diffuse large B-cell lymphoma was suspected at Zhejiang Cancer Hospital. Conclusions Lymphoma is often misdiagnosed, causing delayed treatment initiation and affecting patient outcomes as the disease progresses. The present case demonstrates that the ultrasonic appearance of lymphoma may sometimes be confused with that of tuberculosis. Although ultrasound-guided needle biopsy has a high diagnostic accuracy, it may also cause diagnostic deviation because of insufficient sampling volume. Moreover, owing to the enlargement of multiple lymph nodes due to lymphoma or lymph node tuberculosis, puncturing different lymph nodes may provide different results.